Spatial variability of mangrove epiphytic diatom communities in Lhokseumawe, northern region of the Straits of Malacca: Influence of anthropogenic activities - Muhammad Muaz Munauwar; Baidhawi Baidhawi; Syahrial Syahrial; Muhammad Hatta; Arina Ruzanna; Munawar Khalil (Estuarine, Coastal and Shelf Science, 2026)

The Potential of Inorganic Nanocarriers in Enhancing the Effectiveness of Ciprofloxacin: Review - Rayhan Izzan Fahrezi; Muhammad Hatta Prabowo; Rochmy Istikharah (Next Research, 2026)

In vitro regeneration and biotechnological advances in tissue culture of Zingiber officinale Roscoe: a comprehensive review - Nisar Ahmad Zahid; Uma Rani Sinniah; Muhammad Asyraf Md Hatta; Dzarifah Zulperi; Jutta Papenbrock; Mansor Hakiman (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Genomic characterization of Burkholderia glumae K6 and B. gladioli UPMBG7: causal agents of bacterial panicle blight in Malaysia - Adam Zafdri Md Zali; Siti Izera Ismail; Norsazilawati Saad; Muhammad Asyraf Md Hatta; Mohd Razi Ismail; Mohd Termizi Yusof; Mansor Hakiman; Syari Jamian; Sumaiyah Abdullah; Dzarifah Zulperi (European Journal of Plant Pathology, 2026)
Bacterial panicle blight (BPB), caused by Burkholderia glumae and B. gladioli , is a major threat to rice in Malaysia, with potential yield losses up to 75%. In June 2021, BPB symptoms were detected in Kedah rice fields. Isolates were identified through phenotypic traits, pathogenicity tests, and molecular analysis (16S rRNA and gyrB sequencing). Whole-genome sequencing of B. glumae K6 and B. gladioli UPMBG7 was performed using the Illumina NovaSeq 6000 platform. The assembled draft genome of B. glumae K6 contained 210 contigs, with a total genome size of 6.57 Mbp, 68.33% G + C content, and 5,641 coding sequences (CDS). It harbored toxoflavin biosynthesis genes ( toxABCDE , toxJ ) and a Type III secretion system (T3SS), contributing to its pathogenicity. B. gladioli UPMBG7 contained 124 contigs, with a total genome size of 8.22 Mbp, G + C content of 67.99, and 7,022 coding proteins. B. gladioli lacked the toxI gene for toxoflavin production but compensated with pyoverdine siderophore genes ( pvdA ), which facilitate iron acquisition. These findings highlight divergent infection mechanisms, with B. glumae relying on toxoflavin-mediated virulence and B. gladioli on resource competition. The genomic insights support the development of resistant rice cultivars, biological controls, and molecular diagnostics to improve BPB management in Malaysia.

Seawater intrusion and mud volcanism impact the groundwater geochemistry of small Bornean islands - Chin Yik Lin; Baba Musta; Mohd. Harun Abdullah; Fera Cleophas; Feona Isidore; Muhammad Hatta Roselee; Alfonso O. Mucci (Chemical Geology, 2025)

Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Setia Sari Girsang; Rowena L. Castillo; Mahyuddin Syam; Zulkifli Zaini; Sunendar Kartaatmadja; Suyamto; Judith Carla Dela Torre; Irish Lorraine B. Pabuayon; Romalene A. Limpiada; Waluyo; Helmi; Samijan; et al. (Field Crops Research, 2025)

Impact of vegetation cover and land surface temperature on the seasonal tropospheric NO2 level variation from satellite observation - Muhammad Rendana; Muhammad Hatta Dahlan; Febrinasti Alia; David Bahrin; Rosihan Pebrianto; Puteri Kusuma Wardhani (Advances in Space Research, 2024)

Opportunity for genome engineering to enhance phosphate homeostasis in crops - Siti Nor Akmar Abdullah; Norazrin Ariffin; Muhammad Asyraf Md Hatta; Nurashikin Kemat (Physiology and Molecular Biology of Plants, 2024)

Advancement in modern breeding and genomic approaches to accelerate rice improvement: speed breeding focus - Fatin’Alyaa Zainuddin; Mohd Razi Ismail; Muhammad Asyraf Md Hatta; Shairul Izan Ramlee (Euphytica, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

High prevalence of multiple antibiotic resistance in fermented food-associated lactic acid bacteria in Malaysia - Yuli Haryani; Nadrah Abdul Halid; Goh Sur Guat; Mahmud Ab Rashid Nor-Khaizura; Muhammad Asyraf Md Hatta; Suriana Sabri; Son Radu; Hanan Hasan (Food Control, 2023)

Hexavalent chromium contamination in groundwater and its implication to human health: a Monte Carlo model approach in Indonesia - Ratna Dwi Puji Astuti; Anwar Mallongi; Ridwan Amiruddin; Muhammad Hatta; Annisa Utami Rauf (Sustainable Water Resources Management, 2023)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)